Modelling And Estimation Of Cutting Forces During Milling Using Finite Element Analysis - Satish Kumar, Arun Kumar Gupta, Smeer Sharma (International Journal of Advanced Science and Technology, 2020)
The cutting force impacts the dimensional accuracy due to deflection in tool and workpiece in milling operation. Modeling of Forces in metal cutting plays a significant role for a large number of purposes, including estimation of tool life, chatter forecast, thermal examination, and tool observation. In this paper, a cutting force model for end milling has been proposed to foresee the radial and peripheral cutting force. Because of the limited component strategy approach, the Finite element model been anticipated the transient temperature appropriations and came about flexible plastic misshapenness actuated during the processing of 2.5D end processing parts comprising highlights like openings, steps, pockets, and so forth. The model prediction has been validated with the experimental observation of cutting forces during end milling of Inconel625.